Vaccine Adjuvants Differentially Affect Kinetics of Antibody and Germinal Center Responses - Pedersen, Gabriel Kristian; Wørzner, Katharina; Andersen, Peter; Christensen, Dennis (Frontiers in Immunology, 2020)
Aluminum salts and squalene based oil-in-water emulsions (SE) are widely used adjuvants in licensed vaccines, yet their mechanisms are not fully known. Here we report that induction of antibody responses displays different kinetics dependent on the adjuvant used. SE facilitated a rapid antibody response in contrast to aluminum hydroxide (AH) and the depot-forming cationic liposome-based adjuvant (CAF01). Antigen given with the SE adjuvant rapidly reached follicular B cells in the draining lymph node, whereas antigen formulated in AH or CAF01 remained at the site of injection as a depot. Removal of the injection site early after immunization abrogated antibody responses only when antigen was given in the depot-forming adjuvants. Despite initial delays in B cell activation and germinal center (GC) formation when antigen was given in depot-forming adjuvants, the antibody levels reached higher magnitudes than when the antigen was formulated in SE. This study demonstrates that the kinetic aspect of antibody responses is critical in adjuvant benchmarking and suggests that the optimal vaccination regime depends on the adjuvant used.